A study of liquid-based cytology in cervical smears - Bolla Phani Meghana; Renuka Inuganti Venkata; Ramya Chitturi; Durga Prasad Baddula; Kolla Sireesha (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Cervical cancer is a major health problem. It ranks second in mortality affecting the world population. Cervical cancer has the advantage that it takes a long time for it to develop. During this time it can be diagnosed and treated properly. For this purpose pap smears (cervical smears) are routinely screened for pre-malignant lesions using Liquid Based Cytology.Purpose: The purpose is to study the prevalence of cervical lesions by EZI PREP method and to determine the prevalence of cervical lesions in various age groups.Material and Methods: This was a prospective study done in the Department of Pathology. All the data regarding the patient was recorded in a predefined proforma. The sample taken by using an endocervical brush was immersed in a vial and collected at a cytopathology laboratory for further processing by the EZIPREP method.Results: A total of 1500 cervical smears were taken into the study. The age group of females ranged from 20-80 years. All the satisfactory smears were evaluated. Inflammatory smears, infectious smears, and smears with epithelial cell abnormalities were identified in the present study. Bacterial vaginosis was the most common infectious condition found in the present study. The most common age group for epithelial cell abnormality in the present study was 41-50 years. The most common epithelial cell abnormality in the present study is High grade squamous intraepithelial lesion followed by Low grade squamous intraepithelial lesion.Conclusion: Out of the 1500 LBC smears studied, the majority (1134) of the smears studied were inflammatory. Epithelial cell abnormalities were found in 21 cases and the most common age group of epithelial abnormalities was the fifth decade.